2020
DOI: 10.1186/s12885-020-07458-0
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in Moroccan elderly: the first multicenter transverse study exploring the sociodemographic characteristics, clinical profile and quality of life of elderly Moroccan cancer patients

Abstract: Background Moroccan incidence of cancer is increasing with the lengthening of life expectancy. Data regarding elderly Moroccan cancer patients are lacking. In the context of our project aiming to develop an adapted version of the Comprehensive Geriatric Assessment CGA to the Moroccan population, we launched the first Moroccan multicenter transverse study to explore the characteristics of elderly Moroccan cancer patients. Methods The study was conducted in nine Moroccan medical oncology departments. Patients … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
1
11
1
Order By: Relevance
“…Furthermore, when comparing groups of institutionalized elders, the average age does not exceed 71 years; this result does not corroborate with those in the literature [12,13]. A survey revealed that the risk of institutionalization is higher among people over 80 years of age [2,11,12].…”
Section: Socio-demographic and Economic Characteristicscontrasting
confidence: 64%
See 2 more Smart Citations
“…Furthermore, when comparing groups of institutionalized elders, the average age does not exceed 71 years; this result does not corroborate with those in the literature [12,13]. A survey revealed that the risk of institutionalization is higher among people over 80 years of age [2,11,12].…”
Section: Socio-demographic and Economic Characteristicscontrasting
confidence: 64%
“…In Morocco, the elderly are expected to represent 23.2% of the population in 2050 against 9.4% in 2014 [11]. The aging urges the government to anticipate and develop new strategies to meet the needs of specialized care of the elderly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Morocco, older adults are expected to represent 23.2% in 2050 against 9.4% in 2014 [ 11 ]. The aging urges the government to develop new strategies to meet the needs of specialized care of older adults.…”
Section: Introductionmentioning
confidence: 99%
“…The aging urges the government to develop new strategies to meet the needs of specialized care of older adults. Thus, there is a significant lack of specialized care intended for this category because there were few residences entirely dedicated throughout the country, managed by non-profit associations [ 11 ]. Furthermore, many older adults are now living alone due to massive youth immigration, falling death rates, major advances in healthcare and social change.…”
Section: Introductionmentioning
confidence: 99%